Daily and weekly external loads in the microcycle: Characterization and comparison between playing positions on amateur soccer - Miguel, Mauro; Cortez, Alberto; Romero, Felix; Loureiro, Nuno; García-Rubio, Javier; Ibáñez, Sergio José (Frontiers in Sports and Active Living, 2022)
Ensuring adequate levels of training and recovery to maximize player performance is critical; however, there are methodological challenges in designing a periodized training program for soccer teams. This study aims to describe and characterize the daily and weekly external load in an amateur soccer team and based on the weighting factors determined by the match reference, compare the external loads between playing positions. Twenty-four amateur soccer players (22.3 ± 1.7 years) were monitored using a global positioning system. Data collected comprises 19 competitive microcycles with a standard structure composed of 3 training sessions (matchday-5, matchday-3, and matchday-2) and one match. Match-reference values were calculated as the mean of the five best values recorded during official matches. The results show, on matchday-5 session, the existence of significant differences between playing positions to relative total distance covered (p = 0.050), relative sprint distance (p = 0.001), relative moderate-intensity accelerations (p < 0.001), relative high-intensity accelerations (p = 0.003), relative moderate-intensity decelerations (p < 0.001), and relative high-intensity decelerations (p = 0.017). On matchday-3 session, there are significant differences to relative very high-speed running distance (p = 0.017) and relative moderate-intensity decelerations (p = 0.014). On matchday-2 session, there are significant differences to relative high-speed running distance (p = 0.025), relative very high-speed running distance (p = 0.008), and relative moderate-intensity decelerations (p < 0.001). Weekly significant differences are observed between the playing positions to relative moderate-intensity accelerations (p = 0.002), relative high-intensity accelerations (p < 0.001), and relative moderate-intensity decelerations (p < 0.001). The weekly load is characterized by a greater weighting on accelerations and decelerations, compared to distances at very-high speed and sprint. The training loads must respect a standard training model that contemplates the individualization of the physical demands of the match, for each playing position, as for each individual.